Lithological mapping and spectroscopic studies of carbonatite and clinopyroxenite from Hogenakkal carbonatite complex, India - Saraah Imran; Sourav Bhattacharjee; Ajanta Goswami; Aniket Chakrabarty (Applied Computing and Geosciences)
The Paleoproterozoic Hogenakkal carbonatite complex, situated within the Mettur shear zone, Southern Granulite Terrain, Tamil Nadu, India, is known for its enigmatic carbonatite-clinopyroxenite association and lithology specific rare earth elements (REE) mineralization. The complex comprises two types of carbonatites (silicate-rich carbonatite-I, and silicate-poor carbonatite-II), intruding the clinopyroxenite as isolated pods or ovoid bodies, and are together emplaced within the granulite country rocks. This study employs Landsat 8 multispectral data to map the spatial distribution and extent of the clinopyroxenite dykes. These dykes serve as geological tracers for locating the spatially associated carbonatite bodies. In addition, the present work investigate the spectroscopic properties of REE-bearing carbonatites and clinopyroxenite. Petrography, Raman spectroscopy of minerals, and spectroradiometric measurements of rock samples support the interpretations derived from Principal Component Analysis (PCA), Spectral Angle Mapper (SAM), Support Vector Machine (SVM), Decision Tree, and Random Forest algorithms, thereby aiding in the identification of lithological variations and potential clinopyroxenite occurrences. Carbonatite-II shows more prominent REE absorption features compared to carbonatite-I. This is consistent with petrographic observations and Raman spectroscopy, which show that the REE mineralization in carbonatite-II is dominated by monazite-(Ce) and hydroxylbastnäsite-(Ce), whereas carbonatite-I contains allanite-(Ce) as the primary REE-bearing phase. This study exhibits the efficacy of Landsat series data and non-destructive spectroscopic methods for preliminary mineral exploration and evaluating REE potential before detailed field investigation.